INDUSTRI BUDAYA DALAM HUBUNGAN BILATERAL KOREA SELATAN-INDONESIA - Pramesti, Dhia Syahla; Jamaan, Ahmad (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2023)
This research examines the development of South Korea's cultural industry after the 1990s economic crisis, particularly in relation to Indonesia. It explores how South Korea successfully integrated its culture with North Korea, leading to the global phenomenon known as the Korean Wave. The South Korean government played a crucial role in advancing the cultural industry as part of its soft power and public diplomacy strategy. This study adopts a qualitative approach with the theoretical framework of transnationalism perspective and public diplomacy theory. Secondary data were collected through literature reviews from various sources, including books, journals, online articles, and mass media. The findings show that the Korean Wave has captured the attention of nearly all Asian, American, and European countries, including Indonesia. The Korean Wave has had a positive economic impact on South Korea, contributing to the country's Gross Domestic Product (GDP). Moreover, it has opened up cultural cooperation opportunities between South Korea and Indonesia. The Indonesian Wave has started to emerge in South Korea with the introduction of Indonesian K-Pop and K-Drama. South Korea actively promotes its culture in Indonesia through bilateral cooperation and cultural events. The popularity of K-Drama and K-Pop in Indonesia has influenced the culture and lifestyle of its people. Consequently, the post-economic crisis development of South Korea's cultural industry has had a positive impact on the bilateral relationship between South Korea and Indonesia through the Korean Wave. The South Korean cultural industry has become an effective tool of public diplomacy to strengthen relations with other countries. Keywords: Korean Waves, South Korean Diplomacy, South Korea-Indonesia Bilateral Relations.